A bit-Loaded OFDMA for in-home power line communications - Hayasaki, T.; Umehara, D.; Denno, S.; Morikura, M. (2009 IEEE International Symposium on Power Line Communications and Its Applications, 2009)
The in-home broadband power line communication (PLC) is drawing attention to us lately. The broadband PLC has regulation issues for the coexistence with shortwave wireless systems. Therefore, orthogonal frequency division multiplexing (OFDM) is adopted for the broadband PLC. On the other hand, the power line channels suffer from frequency selective fading. It is effective to load appropriate bits on each subcarrier in the OFDM for PLC. In this paper, we propose a bit loading algorithm that maximizes the bit rate by optimizing not only the bit quantity on each subcarrier but also the whole code rate of the forward error correction (FEC) code subject to constraints on the total bit error rate (BER) and power on each subcarrier. Furthermore, we investigate orthogonal frequency division multiple access (OFDMA) as a multiple access scheme on the in-home power line networks. We show that the proposed OFDMA scheme is superior to a time division multiple access (TDMA) scheme from the viewpoint of throughput by computer simulations.